Experimental study on normal deformation characteristics of filled rock joints with typical fluctuation morphology - Luo, Zhanyou; Zheng, Wei; Du, Shigui; Huang, Man; Wang, Changshuo (Frontiers in Earth Science, 2023)
Uneven deformation of filled rock joint under ground stress is easy to cause instability in engineering rock mass. Moreover, fluctuation morphology and filling are main factors affecting the normal deformation of filled rock joint. In order to study the effect of filling degree and morphology fluctuation degree on normal deformation of filled rock joint, systematic experimental study was conducted. Firstly, rock joints with JRC (rock joint roughness coefficient) of 1,5, 9, 13 and 17 were selected based on Barton's typical curves. Then, the filled rock joint samples were made by self - developed filled rock joint sample mold and 3D engraving technology. Lastly, compression tests were carried out to analyze the effect of filling degree and morphology fluctuation degree on normal deformation characteristics of filled rock joint. Results show that the filling degree significantly affects normal deformation of filled rock joint sample. The normal deformation of filled rock joint have a nonlinear relationship with normal stress. Power function equation can well represent the normal closure deformation behaviour of filled rock joint. Additionally, the relationship between maximum closure deformation of filled rock joint and filling degree is established based on Bandis empirical formula. The proposed equation takes into account the effect of filling degree by replacing the rock joint opening with filling thickness, and the predicted values agree well with the experimental results.